Medical student’s perception of their academic performance in emergency remote teaching during the Covid-19 pandemic (Research, Society and Development, 2022)
Due to the pandemic related to the new coronavirus (SARS-CoV-2). which causes the disease entitled "Covid-19". And the effects of the quarantine and social distancing taken by the population the face-to-face classes of about 1.5 billion students in 165 countries were suspended. This study therefore is aimed to evaluate the perception of medical students about academic performance in emergency remote teaching during the Covid-19 pandemic. A descriptive quantitative cross-sectional study was carried out with 226 medical students from 4 medical institutions in Alagoas. The research uses as a data collection instrument a virtual questionnaire on Google Forms®️ of an anonymous and voluntary nature being disseminated through applications and social networks and intended for all medical students in Alagoas. The results obtained highlight students' interest in maintaining their studies remotely. However the lack of means to access and use such technologies as well as socio-economic situations and the lack of motivation and influence of the home environment proved to be determinant factors for the continuity and effectiveness of the studies.